1997
DOI: 10.1097/00006534-199705000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Tissue Assay: A Measurement of Capsular Levels from Chemotherapeutic Port-a-Catheter Devices

Abstract: A previous nonblinded study has suggested beneficial effects from hyperbaric oxygen treatment of superficial partial-thickness radiation burns in human volunteers. This protocol was designed to either confirm or challenge these previous findings in a randomized, blinded format. Twelve healthy, nonsmoking volunteers (7 males, 5 females) participated. All were screened for contraindications to hyperbaric oxygen therapy (acute sinusitis, otitis media, pneumonia, pregnancy, active cancer, pneumothorax) and given a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 32 publications
1
4
0
1
Order By: Relevance
“…It is possible that HBOT increases the oxygenation of hypoxic tissue that may not survive without additional oxygen during ischemia. 25 The present study demonstrated faster epithelialization in the intervention group versus the control group, which supports the conclusion that adequate oxygen is mandatory for wound healing.…”
Section: Discussionsupporting
confidence: 88%
“…It is possible that HBOT increases the oxygenation of hypoxic tissue that may not survive without additional oxygen during ischemia. 25 The present study demonstrated faster epithelialization in the intervention group versus the control group, which supports the conclusion that adequate oxygen is mandatory for wound healing.…”
Section: Discussionsupporting
confidence: 88%
“…In the present review, of the 11 trials applying this strategy, 3 used stops in the decompression to prevent decompression sickness, 35 , 36 , 38 and 1 trial administered 100% oxygen during decompression. 34 Other trials did not mention the risk of decompression sickness or the way that this risk was minimalized. The authors of the study using 100% oxygen during decompression acknowledged that the use of this strategy may have negatively influenced the inertness of the placebo, possibly decreasing the differences in outcome between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the study using 100% oxygen during decompression acknowledged that the use of this strategy may have negatively influenced the inertness of the placebo, possibly decreasing the differences in outcome between the groups. 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperbaric oxygen treatment has been another approach that has previously been used to treat burn wounds [92] and has been shown to improve wound healing in human burn wound models [19]. Turkaslan et al investigated the effects of HBOT in the zone of stasis and reported increased cells in the synthesis stage by 24 hours post-burn, increased radioactive uptake by 5 days post-burn, and decreased necrosis overall in the treatment group [75].…”
Section: Discussionmentioning
confidence: 99%